Improvement in non-specific immunity and disease resistance of barramundi, Lates calcarifer (Bloch), by diets containing Daphnia similis meal. Issue 1 (May 2015) - Chiu, Shieh-Tsung; Shiu, Ya-Li; Wu, Tsung-Meng; Lin, Yu-Syuan; Liu, Chun-Hung
Abstract A 42-day study was conducted with barramundi, Lates calcarifer, to evaluate the effects of Daphnia meal derived from Daphnia similis on fish growth, immune response, and disease resistance to Aeromonas hydrophila. Three isonitrogenous (45%) and isolipid (10%) experimental diets were formulated to contain 0% (control), 5% (D5), and 10% (D10) Daphnia meal. Growth was depressed when fish were fed with the D10 diet for 42 days compared to control. However, the growth in fish fed with control and D5 diets for 42 days was not significantly different. By day 42, the leukocyte phagocytic activity and respiratory burst activity were significantly increased in D5 and D10 groups compared to control. Mx gene expression in the spleen and head kidney of fish after being injected with nerve necrosis virus was also significantly up-regulated in both groups compared to control. In an increased immune response, D5 and D10 fish had significantly higher survival rates than control after being challenged by A. hydrophila. Therefore, we suggest that a 5% Daphnia-meal diet could improve the barramundi immune response and disease resistance without a negative impact on growth.